Clara Sales - Right Ventricular vs Left Bundle Branch Pacing-Induced Changes in ECG Depolarization and Repolarization - Sales, Clara (Jornada de Jóvenes Investigadores del I3A, 2022)
Right Ventricular vs Left Bundle Branch Pacing-Induced Changes in ECG Depolarization and Repolarization